Ethanolic extract of cotinus coggygria leaves attenuates crystalluria and kidney damage in ethylene glycol induced urolithiasis in rats - ERTAŞ, BÜŞRA; ŞEN, ALİ; ŞENER, TARIK EMRE (My University, 2023)
Nephrolithiasis is a common cause of kidney insufficiency. Nephrolithiasis is proven to be the result of various biochemical and inflammatory processes that result in crystal formation and subsequent aggregation. Cotinus coggygria L. (CCog) is a plant extract which has been used as a Turkish remedy for kidney stones. With this study, we planned to evaluate the effects of CCog extract in ethylene glycol (EG) induced nephrolithiasis model in rats. Materials and Methods The study group comprised of 32 Wistar albino rats which were divided into Control (C), EG, CCog Prophylaxis (CC+EG+CC) and CCog Treatment (EG+CC) groups. Stone formation was induced by adding EG (0.75%) into rat’s drinking water. Normal drinking water was given to Control group for 8 weeks. Throughout the study period of 8 weeks, EG group was given only EG (0.75%) and CC+EG+CC group was given both EG and CCog. In EG+CC group, EG (0.75%) was given for 8 weeks whereas CCog was given for the last 4 weeks. After the 8th week, 24-hours urine samples were collected. Rats were then sacrificed and kidney tissue samples were harvested. Results Metabolites (calcium, citrate) and creatinine in 24h urine samples were decreased in CC+EG+CC and EG+CC groups. While hyperoxaluria was observed in the EG group, oxalate levels weresimilar to control levels in the P-CCog and C-CCog groups. The N-acetyl-β-glucosaminidase and myeloperoxidase activities were both increased in EG group and these parameters were significantly decreased upon CCog treatment. Conclusion We can conclude that Cotinus coggygria extract can have beneficial effect on lowering concentration of stone-forming metabolites in urine and consequently protect renal tissues from damage due to nephrolithiasis. Cotinus coggygria extract can be considered as a potential prophylactic and therapeutic option in high-risk stone formers. Also, our data confirm ethnobotanical use of CC against nephrolithiasis.

Giriş: Nefrolitiazis böbrek yetmezliğinin sık bir sebebidir. Yapılan araştırmalar oksidatif stresin, kristal oluşumuna ve agregasyonuna sebep olarak taş oluşumunun kompleks biyokimyasal mekanizmalarının temelinde buluduğunu göstermiştir. Cotinus coggygria L. (CCog), geleneksel Türk tıbbında çeşitli hastalıklarda tedavi amaçlı kullanılmaktadır. Bizim çalışmamızın amacı, sıçanlarda etilen glikol (EG) ile oluşturulan üriner sistem taş modelinde CCog ekstraktının önleyici ve tedavi edici etkilerini araştırmaktır. Materyal ve Metot: Wistar albino cinsi 32 sıçan rastgele olarak Kontrol (C), EG, Önleyici (CC+EG+CC) ve tedavi edici (EG+CC) olacak şekilde gruplara ayrıldı. Ürolitiazis modeli geliştirmek için içme suyuna EG (%0.75) eklendi. Kontrol grubu 8 hafta içme suyu ile beslendi. 8 hafta boyunca EG grubu EG (%0.75) ve CC+EG+CC grubu hem EG hem de CCog ekstresi aldı. EG+CC grubu 8 hafta EG (%0,75) alırken son 4 hafta CCog ekstresi aldı. Deney sonunda 24 saatlik idrar örnekleri toplandı ve dekapitasyon sonrası böbrek doku örnekleri alındı. Bulgular: İdrar iyon (kalsiyum, sitrat) ve kreatinin seviyeleri hem önleyici hem de tedavi edici gruplarda azaldı. EG grubunda hiperokzalüri görülürken, okzalat seviyeleri CC+EG+CC ve EG+CC grubunda kontrol seviyelerinde izlendi. Ayrıca, EG grubunda artan N-asetil-β-glukosaminidaz ve miyeloperoksidaz aktiviteleri, CCog tedavisi ile anlamlı ölçüde tersine döndürüldü. Sonuç: Sonuçlarımız, Cotinus coggygria ekstresinin taş oluşumunda rol oynayan bileşenlerin idrar konsantrasyonunu azaltabileceğini ve bu şekilde böbrek dokusunda hasar oluşumunu önleyebileceğini desteklemektedir. Bu nedenle üriner sistem taş oluşma riski yüksek olan hastalarda potansiyel bir profilaksi ve tedavi ajanı seçeneği olarak değerlendirilebilir. (NCI-2022-12-20)
Cotinus coggygria yapraklarının etanolik ekstresi sıçanlarda etilen glikolle indüklenen ürolitiyaziste kristalüri ve böbrek hasarını azaltır
Keywords: Ethylene glycol; hyperoxaluria; nephrolithiasis; oxidative stress; renal insufficiency; Etilen glikol; hiperoksalüri; nefrolitiazis; oksidatif stres; böbrek yetmezliği